Applied ecology in India: scope of science and policy to meet contemporary environmental and socio‐ecological challenges. Issue 1 (7th January 2013) - Singh, Navinder J.; Bagchi, Sumanta
Summary: India, a mega‐diverse country in terms of both biodiversity and people, is battling environmental problems on many fronts: chronic dependence on natural resources, dwindling ecosystem services, declining environmental quality, effects of climate change and a biodiversity crisis. We review the current focal areas and infrastructure for ecological research and education in India, along with the surrounding legal and policy aspects of related socio‐economic issues. Currently, ecological and applied research is predominantly focused on charismatic species within protected areas. This scope could be broadened beyond organismal biology towards functional landscapes and ecosystems; the education system also needs to promote ecology as a career choice for scientists. Expectedly, many environmental challenges are generic in nature, occur in other regions of the world, are primarily biophysical in origin but extend into human dimensions; some challenges are socio‐political and have implications for biodiversity conservation. Synthesis and applications . India's environmental concerns include, but are not restricted to, the biodiversity crisis. The biodiversity crisis, in turn, includes, but is not restricted to, the most charismatic species. Greater integration and alignment among the mandates of government agencies, scientists, policymakers and educators are needed to meet contemporary environmental issues. Abstract : India's environmental concerns include, but are not restricted to, the biodiversity crisis. The biodiversity crisis, in turn, includes, but is not restricted to, the most charismatic species. Greater integration and alignment among the mandates of government agencies, scientists, policymakers and educators are needed to meet contemporary environmental issues.